Aplikasi Berbasis Smartcard pada Lingkungan Sistem Operasi Windows - Basuki Winoto (Jurusan Teknik Informatika, Fakultas Teknologi Industri, Universitas Islam Indonesia, 2004)
Integrated Circuit Card or commonly named as smartcard is a properiatery devicewhich is based on ISO/IEC 7816 standard. In order to expand smartcard capabilities andinteroperabilites, PC/SC Workgroup defines a specification on interoperabilities between PCand smartcard. With this specification, which also has been implemented by Microsoft asWin32 API, one can develop applications which is using smartcard as small amount datastorage (identification key, password, or else).Smartcard-based applications can be developed in Windows operating systemenvironment easily by using Win32 API library, user interface library or Win32 COM library.The application development itself can be done by using Microsoft Visual C++ or MicrosoftVisual Basic.Keywords: ICC, smartcard, interoperable, PC/SC workgroup, win32